Peningkatan Pengetahuan Penyakit Menular Seksual (PMS) dan Kesadaran Deteksi Dini Kanker Serviks Melalui Edukasi Kesehatan Reproduksi Di Desa Barangka - Indri Aswianti Tamrin; Anggel Ayu Apriza; Wa Ode Arzeti Fahra; Asria Asria; Windiyanti Windiyanti; Nurmin Nurmin (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Sexually Transmitted Diseases (STDs) and cervical cancer remain important reproductive health problems due to low public awareness regarding prevention and early detection. This study aimed to determine community knowledge regarding STDs and awareness of early cervical cancer detection through reproductive health education in Barangka Village. This study used a descriptive observational design involving 111 respondents. Data were collected through interviews, observations, questionnaires, and health education activities. The results showed that 69 respondents (62%) did not know about STDs, while only 42 respondents (38%) had knowledge regarding STDs. In addition, 90 respondents (81%) had low knowledge regarding cervical cancer and early detection. After the educational activities, the community showed increased understanding and awareness regarding reproductive health and the importance of IVA or Pap Smear examinations. The study concludes that reproductive health education can improve public knowledge and awareness regarding STDs and early detection of cervical cancer. Continuous health education is needed to improve community reproductive health